A Laser Cutting Machine Prototype - Tung, Tran Thanh; Tan, Trinh Minh; Minh, Tran Vu (Engineering, Technology & Applied Science Research, 2024)
Nowadays, laser cutting technology stands as one of the most cutting-edge technologies. Not only do laser cutting machines play a crucial role in the mechanical engineering industry, but also in numerous other industries including electronic circuit manufacturing, garment manufacturing, and particularly in the handicraft industry. This study presents a methodology for the design and production of laser cutting machines in Vietnam. A laser cutting machine has been successfully constructed, featuring a straightforward configuration, user-friendly operation, and low cost. The machine has the ability to perform laser cutting on wooden materials, achieving a cutting depth ranging from 1 to 2 mm. The proposed laser cutting machine prototype can cut at a speed of 1000 mm/min, thus meeting the specified requirements.